Orthognathic surgery in the treatment of obstructive sleep apnea syndrome - Azevedo da Silva, Louise Bárbara (2024)
Introduction: Sleep is a fundamental moment in life, essential for physical and mental well-being. During sleep, the body restores itself, strengthening the immune system, improving the cognitive system, and reducing the risk of disease. Obstructive Sleep Apnea Syndrome (OSAS) is a disorder characterized by recurrent episodes of total or partial obstruction of the upper airway during sleep, resulting in pauses in breathing and a drop in blood oxygen levels. Frequent sleep interruptions can lead to excessive daytime sleepiness, fatigue, difficulty concentrating, and irritability, significantly affecting quality of life and performance in daily activities. Not only does this syndrome interfere with sleep quality, but it can also increase the risk of developing high blood pressure and cardiovascular diseases such as heart attacks, strokes, and cardiac arrhythmias. Orthognathic surgery is a procedure that aims to correct craniofacial anomalies, including misalignments of the jaw and maxilla, and can be effective in clearing the upper airway. By repositioning these bone structures, it is possible to widen the airways and improve airflow during sleep, reducing the severity and symptoms of OSAS. Objective: This study aims to analyze the clinical applications and indications of orthognathic surgery in the treatment of Obstructive Sleep Apnea Syndrome (OSAS). Methodology: This is an exploratory bibliographic research, of a descriptive nature, developed from the PubMed/Medline, Virtual Health Library (VHL) and SciELO databases. The search for articles was performed using the descriptors: "Orthognathic Surgery", "Obstructive Sleep Apnea", "Malocclusion" and "Angle Class II". Original articles, literature reviews, and case reports limited to humans, in Portuguese and English, were included. Results: It was observed that orthognathic surgery is not the first line of treatment and is usually reserved for more severe cases or when there is failure with conservative therapies. The technique consists of repositioning the mandible and/or maxilla, resulting in the traction of the tongue forward and away from the pharynx, thus increasing the permeability of the airways. Conclusion: Orthognathic surgery represents a promising and effective approach in the treatment of OSAS, especially for patients with severe upper airway obstructions and who do not respond adequately to other treatment modalities.